Peran Kaum Milenial sebagai Cross-Cutting Interpreters dalam Pengembangan Desa Wisata Pelaga Kabupaten Badung Bali - Fransisco Situmorang; Saptono Nugroho (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2020)
The economic disparity that occurred in Badung Regency, Bali was caused by the rapid development of tourism that does not align with the development of the agricultural sector in the north. This then pushed the Pelaga Tourism Village millennial to urbanize into the southern regions to continue education and to obtain employment. This research aims to analyze the role that millennials can do as cross-cutting interpreters in the development of Pelaga Tourism Village. This research uses qualitative data with two data sources: primary data and secondary data. The data collection techniques used in this research are library studies, observations, interviews, and documentation. In determining the informants is used as a purposive sampling technique. In this study, the data analysis technique used is descriptive-qualitative. The results showed that the role of the millennial generation in the development and management of tourism villages has been very minimal. This is very unfortunate considering the millennial has the ability as cross-cutting interpreters and as well as rich in innovation and much-needed creativity in the development of tourism villages. The role that can be performed by millennials in developing tourist villages is by establishing BUMDes as an organization for tourism village management. Millennials should also conduct mapping and development of several tourism potentials in each Banjar by prioritizing the aspect of diversification. At the marketing and promotion stage, millennials who are technologically literate can utilize digital media as a means to introduce and offer tourism products. Keyword: Millenials, Cross-Cutting Interpreters, Tourism Villages